Microglia show altered morphology and reduced arborization in human brain during aging and Alzheimer's disease. (12th December 2016) - Davies, Danielle S.; Ma, Jolande; Jegathees, Thuvarahan; Goldsbury, Claire
Abstract: Changes in microglia function are involved in Alzheimer's disease (AD) for which ageing is the major risk factor. We evaluated microglial cell process morphologies and their gray matter coverage (arborized area) during ageing and in the presence and absence of AD pathology in autopsied human neocortex. Microglial cell processes were reduced in length, showed less branching and reduced arborized area with aging (case range 52–98 years). This occurred during normal ageing and without microglia dystrophy or changes in cell density. There was a larger reduction in process length and arborized area in AD compared to aged‐matched control microglia. In AD cases, on average, 49%–64% of microglia had discontinuous and/or punctate Iba1 labeled processes instead of continuous Iba1 distribution. Up to 16% of aged‐matched control microglia displayed discontinuous or punctate features. There was no change in the density of microglial cell bodies in gray matter during ageing or AD. This demonstrates that human microglia show progressive cell process retraction without cell loss during ageing. Additional changes in microglia occur with AD including Iba1 protein puncta and discontinuity. We suggest that reduced microglial arborized area may be an aging‐related correlate of AD in humans. These variations in microglial cells during ageing and in AD could reflect changes in neural‐glial interactions which are emerging as key to mechanisms involved in ageing and neurodegenerative disease.